In artificial intelligence (AI) we trust: A qualitative investigation of AI technology acceptance. Issue 3 (21st February 2022) - Hasija, Abhinav; Esper, Terry L.
Abstract: Artificial intelligence (AI) applications are increasingly used to support supply chain management (SCM) activities. However, industry reports and recent research indicate difficulty in implementing AI solutions. This study explores the role of organizational factors in reconciling the differences between the potential SCM benefits of AI and its actual acceptance and use. We apply thematic analysis techniques to explore the marketing materials used by vendors of AI‐enabled software and interviews with organization leaders that have experience with the deployment of AI‐based technologies. The emergent model from our data analysis highlights organizational tactics often used to emphasize AI trustworthiness. Our findings suggest several tactics that could be used to convey that AI is a trustworthy technology. We build on the thematic model to situate the findings as offering theoretical extensions to the "social influence" aspect of UTAUT; and develop a robust call for research related to the effects of AI trustworthiness on internal, upstream, and downstream activities in the supply chain. The results contribute to academic conversations related to the acceptance and use of technology and the growing digitalization of supply chains. We outline managerial implications regarding the role of AI trustworthiness in AI use for managing SCM.